A scalable unified framework of total and allele-specific counts for cis-QTL, fine-mapping, and prediction - Yanyu Liang (Nature Portfolio, 2021)
Methods for eQTL mapping from total and allele-specific gene expression typically are too computationally heavy to apply to large scale studies. Here, the authors describe a computationally efficient method to identify eQTLs, fine-map and predict expression from total and allele-specific gene expression